Teacher’s Questioning Strategies Used in the English Speaking Class of Junior High School - Lulus Irawati; Uphy Riska Nirmalasari; Erlik Widiyani Styati (Yayasan Visi Intan Permata, 2021)
The objective of this research is to identify the types of the teacher’s questioning strategy used in the English speaking class of junior high school. The research was using a qualitative approach. This study was carried out in a teacher and students speaking English in two classrooms. The data were collected from classroom observation and documentation. This study shows that the teacher applies all the questioning strategy. In this case, the types of questioning strategies are strategy are structuring, pitching and putting clearly, directing and distributing, pausing and pacing, prompting and probing, listening to replies and responding and sequencing. The questions are started modals like will and can and auxiliary do and did and linking verbs is and are. The teacher also starts the question with wh-questions like what, when, why, where, who and how questions. The result of this study can make the teacher controls the lesson, guide the students’ response, and promote interaction in classroom. The students can contribute to share, show and express their idea when they are given questions by the teacher.